What Money Could Buy: A Reply to Michael Sandel - Volberg, Mats (Problemos, 2015)
According to Michael Sandel in recent decades we have witnessed a change in our thinking and acting. Namely we have become to think more in terms of economics and we have also started to buy and sell a lot more things. Sandel finds this troubling and presents two arguments: (1) the inequality and fairness argument, which states that such practises help to transfer inequalities, and (2) the corruption argument, which states that such practises corrupt the nature of the thing being bought and sold. It is argued here that neither of those arguments works in the way Sandel intends. It is also shown that a charitable reading allows us to extract a third implicit argument which does not work either. The article ends with a brief discussion of two arguments which show promise in proving Sandel’s point, but unfortunately are left underdeveloped by Sandel.